Domains of language use among Gaddang speakers in Nueva Ecija , Philippines - Asuncion, Zayda S.; Madrunio, Marilu Rañosa (2017)
As a sociolinguistic study, this paper investigated domains of language use among Gaddang speakers, a multilingual ethnic group in the northern part of the Philippines and its possible differences in using Gaddang, Tagalog/Filipino, Ilocano, and English in the public and internal domains considering geographical area, age, gender, economic status, and educational attainment. There were 568 Gaddang speakers who participated in the study. Employing survey questionnaire to gather quantitative data and a semi-structured interview to support quantitative results, the study revealed that the Gaddang speakers used Gaddang, Tagalog, Ilocano, and English in the public and internal domains, but the dominant language preferred is Tagalog. Significant differences in domains of language use were apparent in terms of geographical area, age, socio economic status, and educational attainment in the use of Gaddang and English in the public domain. In the internal domain, the Gaddang speakers vary in their use of Gaddang, Ilocano, Tagalog, and English considering geographical area, age, socio economic status, and educational attainment in the use of Gaddang and English in the public domain. In the internal domain, the Gaddang speakers vary in their use of Gaddang, Ilocano, Tagalog, and English considering geographical area, age socio economic status, and educational attainment. Significant implications on two linguistics phenomena such as language maintenance and language shift can be deduced from the results.
Keywords: Sociolinguistics; Ethnic groups; Gaddangs (Philippine people); Language